Mapping Civil Servants’ Digital Literacy: A Readiness Model for Indonesia’s E-Government Transformation - Nadjib, Abdul; Azhar, Azhar; Prabujaya, Sena Putra; Malek, Jalaluddin Abdul; Khairunnas, Khairunnas (Journal Public Policy, 2025)
This study aims to map the digital literacy competencies of Indonesia’s State Civil Apparatus (ASN) as a foundation for assessing e-government (SPBE) readiness. Focusing on Muara Enim Regency, South Sumatra, the research examines the relationship between ASN characteristics and their levels of digital literacy to develop a comprehensive readiness model. Employing a mixed-method approach with quantitative data from 238 respondents and qualitative validation through interviews, the study utilizes Law et al.’s (2018) Digital Competence Framework alongside the Ministerial Regulation on ASN Competencies. The findings reveal that 60.5% of respondents possess a high level of digital literacy, corroborated by the 2023 SPBE evaluation by KemenpanRB, which rated Muara Enim’s SPBE implementation as “good” (score 3.00). The analysis produces an ASN Digital Literacy Mapping Model consisting of four interrelated dimensions: (1) operationalization of analytical technology tools, (2) digital data and information management, (3) digital interaction and collaboration, and (4) digital security knowledge. This model contributes a new analytical framework for assessing digital readiness within Indonesia’s public sector and supports the integration of digital literacy assessment in SPBE self-evaluation. Although limited to one regency and cross-sectional data, the model provides a replicable foundation for broader regional and longitudinal studies.